Large Gastric Trichobezoar - Alegre Saller, Valdemir José; Reis dos Santos, Rafaela Maria; da Silva Medeiros, Fernanda; Ferretti, Carlos Eduardo (Cirugía del Uruguay, 2025)
A 26-year-old single female patient presented with a non-radiating burning pain in the epigastric region associated with intolerance to fatty foods, which had been present for approximately 6 months. The pain was occasional and had worsened over the past 10 days. She reported experiencing a feeling of early satiety after eating and postprandial abdominal distension. She lost 20 kg during this period.